THE RELATIONSHIP BETWEEN DIGITAL LITERACY AND CRITICAL THINKING SKILLS IN GRADE V IN ELEMENTARY SCHOOL - Saadah, Anisah; Imamudin, Imamudin; Munawaroh, Munawaroh (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
The study aims to determine the relationship between digital literacy and critical thinking skills of fifth-grade students at SDN Banjarsari 2, Serang City. Digital literacy is a very important skill in the digital era, especially in supporting technology-based learning processes. Critical thinking skills are 21st-century competencies that need to be developed early so that students are able to analyze, reason, and draw critical or logistical conclusions. In this study, the method used is a quantitative method with a correlational approach, the sample in this study were fifth-grade students of SDN Banjarsari 2, Serang City. The instrument in this study used a questionnaire to measure digital literacy and to measure critical thinking skills, a test instrument in the form of 10 essay questions was used. The results of the analysis of this study indicate a significant relationship between digital literacy and students' critical thinking skills. The higher the students' digital literacy, the higher their critical thinking skills. This study shows the importance of digital-based learning in developing critical thinking skills in elementary schools.